Artistic Responses to Travel in the Western Tradition
1 online resource (xiv, 258 pages)
Keywords: "In an era when ease of travel is greater than ever, it is also easy to overlook the degree to which voyages of the body--and mind--have generated an outpouring of artistry and creativity throughout the ages. Exploration of new lands and sensations is a fundamental human experience. This volume in turn provides a stimulating and adventurous exploration of the theme of travel from an art-historical perspective. Topical regions are covered ranging from the Grand Tour and colonialism to the travels of Hadrian in ancient times and Georgia O'Keeffe's journey to the Andes; from Vasari's Neoplatonic voyages to photographing nineteenth-century Japan. The scholars assembled consider both imaginary travel, as well as factual or embellished documentation of voyages. The essays are far-reaching spatially and temporally, but all relate to how art has documented the theme of travel in varying media across time and as illustrated and described by writers, artists, and illustrators. The scope of this volume is far-reaching both chronologically and conceptually, thereby appropriately documenting the universality of the theme to human experience."--Provided by publisher.